Effect of pilocarpine mouthwash on salivary flow - Bernardi,R. (2002)
Pilocarpine is a cholinergic agonist that increases salivary flow and has been used to treat xerostomia. Oral intake is the most frequent route of administration. Adverse effects are dose-dependent and include sudoresis, facial blushing and increased urinary frequency. The objective of the present study was to evaluate the effects of topical pilocarpine solutions as mouthwashes on salivary flow and their adverse effects on healthy subjects. Forty volunteers received 10 ml 0.5, 1 and 2% pilocarpine solutions or 0.9% saline in a randomized, double-blind, placebo-controlled manner. Salivation was measured before and 45, 60 and 75 min after mouth rinsing for 1 min with 10 ml of saline or pilocarpine solutions. Vital signs were measured and ocular, gastrointestinal and cardiovascular symptoms, anxiety and flushing were estimated using visual analog scales. There was a dose-dependent increase in salivation. Salivation measured after 1 and 2% pilocarpine (1.4 ± 0.36 and 2.22 ± 0.42 g, respectively) was significantly (P<0.001) higher than before (0.70 ± 0.15 and 0.64 ± 0.1 g), with a plateau between 45 and 75 min. Cardiovascular, visual, gastrointestinal and behavioral symptoms and signs were not changed by topical pilocarpine. Mouth rinsing with pilocarpine solutions at concentrations of 1 to 2% induced a significant objective and subjective dose-dependent increase in salivary flow, similar to the results reported by others studying the effect of oral 5 mg pilocarpine. The present study revealed the efficacy of pilocarpine mouthwash solutions in increasing salivary flow in healthy volunteers, with no adverse effects. Additional studies on patients with xerostomia are needed.